2015
DOI: 10.1002/adfm.201501880
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Modulus, Strength, and Ductility in Adhesive Design Using Biomimetic Polymer Chemistry

Abstract: High‐performance adhesives require mechanical properties tuned to demands of the surroundings. A mismatch in stiffness between substrate and adhesive leads to stress concentrations and fracture when the bonding is subjected to mechanical load. Balancing material strength versus ductility, as well as considering the relationship between adhesive modulus and substrate modulus, creates stronger joints. However, a detailed understanding of how these properties interplay is lacking. Here, a biomimetic terpolymer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 53 publications
1
71
0
Order By: Relevance
“…Although the adhesion mechanism is not completely known, glue proteins secreted by marine mussels bind strongly to all inorganic and organic surfaces in aqueous environments. Hence several papers were published in order to explain the peculiar properties of this kind of proteins and develop biomimetic adhesives or coatings by modifying synthetic polymers using moieties similar to DOPA, suitable for making films [246]. However, in this approach, natural proteins were not used up to now due to lack of protein availability, and for this reason recombinant approaches are currently under study.…”
Section: Emerging Proteins From Animal Kingdommentioning
confidence: 99%
“…Although the adhesion mechanism is not completely known, glue proteins secreted by marine mussels bind strongly to all inorganic and organic surfaces in aqueous environments. Hence several papers were published in order to explain the peculiar properties of this kind of proteins and develop biomimetic adhesives or coatings by modifying synthetic polymers using moieties similar to DOPA, suitable for making films [246]. However, in this approach, natural proteins were not used up to now due to lack of protein availability, and for this reason recombinant approaches are currently under study.…”
Section: Emerging Proteins From Animal Kingdommentioning
confidence: 99%
“…Recently, Wilker and co‐workers synthesized a series of polystyrene‐based mussel‐inspired adhesives by the copolymerization of 3,4‐dimethoxybenzene ethylene and styrene, which showed excellent adhesive ability on metal, glass, and plastic substrates . Although significant achievements have been made in this area, however, the use of expensive raw materials, such as dopamine, 3,4‐dimethoxybenzaldehyde, and dopamine methacrylamide and the sophisticated preparation steps seriously limited their practical application …”
Section: Introductionmentioning
confidence: 99%
“…Mussel byssus proteins (Mfps), a group of proteins secreted from mussel byssus being rich in catecholic amino acid, 3,4-dihydroxyphenyl-l-alanine (DOPA), are well known for their strong adhesive properties at wet/underwater conditions. [1][2][3] Scientific studies have shown that DOPA plays a key role for the strong adhesion, due to the formation of (2 of 9) 1700206 achievements have been made in this area, however, the use of expensive raw materials, such as dopamine, [22] 3,4-dimethoxybenzaldehyde, [23] and dopamine methacrylamide [24] and the sophisticated preparation steps [25] seriously limited their practical application. [26] In previous work, we had developed a simple and efficient method to synthesis a poly(vinyl alcohol) (PVA)-based biomimetic polymer with pendent catechol groups via a one-step acetal formation reaction from two cheap commercially available materials: PVA and 3,4-dihydroxybenzaldehyde, which could act as hot curing adhesives and exhibited excellent bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Mussel-inspired catechol chemistry opens a versatile approach to build functional materials for surface modification due to their fascinating chemical properties, such as outstanding adhesive properties, strong metal-chelation abilities, and redox characteristics. [1][2][3][4][5][6][7][8][9][10][11][12] These biomimetic materials form functional coatings on the surface of a wide range of substrates. [13][14][15][16][17] Among these coatings, antibacterial coating is very important and has been extensively studied, since the demand to free the surfaces from bacteria attaching and proliferating continues to increase, especially for biomedical devices.…”
Section: Introductionmentioning
confidence: 99%